Cynical theories : how activist scholarship made everything about race, gender, and identity-and why this harms everybody - Pluckrose, Helen; Lindsay, James (Pitchstone Publishing, 2020)
"Outlines the origin and evolution of postmodern thought over the last half century and argues that the unchecked spread and application of postmodern ideas -- from academia, to activist circles, to the public at large - presents an authoritarian ideological threat not only to liberal democracy but also to modernity itself"--